An amateur sleuth's guide to murder - Cahoon, Lynn (Cahoon, Lynn. Bainbridge Island mystery., 2025)
"TIP #1: WHAT DOESN'T KILL YOU COUNTS AS WORK EXPERIENCE. Meg Gates could use a guidebook for life. Indeed, she's faced some challenges. She dropped out of college to work for a tech startup that failed--and her fiancé just took her bridesmaid to Italy on what was supposed to be Meg's honeymoon. Now, at twenty-six, Meg has taken the ferry ride of shame from Seattle back to Bainbridge Island to live with her family. At least she has her rescue cocker spaniel, Watson, by her side. But it's Meg who could use a rescue--and she's hoping it will come in the form of a part-time gig doing research for a bestselling mystery writer. TIP #2: WRITE WHAT YOU KNOW--OR WHAT YOU WANT TO KNOW. That's when the lightbulb goes on: Meg will write her own guidebook--a manual on criminal investigation. But before she can impress her new boss with her pet project, the author's manager is found dead on the rocks beneath the author's Gothic mansion. Now it's time to put her guide to the test, as Meg sets out to clear her employer of suspicion and solve the crime. But there's one important caveat she'll have to add to her guide--TIP #3: BEWARE OF UNKNOWN DANGERS"--